Analisis dan Bauran Pemasaran Prospek Pengembangan UMKM Desa Karawana Kecamatan Dolo Kabupaten Sigi - Virta Nurul Arini; Kurniansi Kurniansi; Ni Made Suwitri Parwati; Fera Fera (Universitas Kristen Indonesia Toraja, 2023)
Micro, Small and Medium Enterprises (MSMEs) in Karawana Village are one of the community's priorities in increasing economic income. MSMEs that are developing in Karawana Village include culinary, trade, animal husbandry and agriculture businesses. This study aims to implement a marketing mix that is directly related to UMKM Karawana Village, Dolo District, Sigi Regency. The implementation method used in this community service activity is carried out in several stages, namely observation, interviews, and evaluation. Based on the results of the interviews, there is an exposure to the 4P Marketing Mix variables that have been implemented in Micro Business actors in Karawana Village, Dolo District, Sigi Regency, product (Price), distribution or place (Place), and promotion (Promotion). Prospects for the Development of Micro, Small and Medium Enterprises have several comparative advantages over large businesses. These advantages include: In terms of capital, the development of small businesses requires relatively small business capital compared to large businesses.